Do Elderly Patients Use Patient-Controlled Analgesia Medication Delivery Systems Correctly?. (July 2015) - Brown, Amanda; Boshers, Bridget; Chapman, Lindsey Floyd; Huckaba, Kim; Pangle, Mandi; Pogue, Lisa C.; Potts, Maegan; Ray, Elizabeth; Thomason, Nicole; Poynter, Andrea; MacArthur, Susan
<x xml:space="preserve">Abstract</x> BACKGROUND: Although prior studies have shown patient-controlled analgesia (PCA) to be appropriate for use by children and adults, no studies have specifically evaluated the ability of elderly patients to use the technology correctly. PURPOSE: To determine whether elderly, postoperative patients can properly use PCA devices. METHODS: Using a descriptive study design, a convenience sample of elderly, postoperative orthopedic patients was observed while using a PCA device and surveyed about the proper use of the device. Participants were observed and surveyed 12 to 20 hours after admission to the postoperative patient care unit. Frequency and amount of analgesic medication administration over the postoperative time period were also recorded. Data were summarized with descriptive statistics and multiple regression analysis was used to determine whether confounding variables explained problems using the PCA device correctly. RESULTS: A total of 58 orthopedic patients were studied during the first day after surgery. Patients had used the PCA device for 16.6 ± 3.0 (mean ±SD) hours at the time of the observation and survey. Virtually all patients correctly identified and depressed the PCA activation button when instructed, knew when to use the PCA device, and who was allowed to depress the PCA button. Slightly more than half of the patients (57%) correctly identified how often they could have PCA medication, with 38% not sure of PCA medication frequency. The PCA medication was requested an average of 23.3 ± 52.7 times during the study period. The majority of the patients (86%) requested PCA medication less than 25% of the times that they could receive PCA medication. All patients in the study had PCA devices programmed to deliver up to 5 doses per hour of PCA medication, yet an average of 11.2 ± 10.8 doses of PCA medication were actually delivered during the entire study period (average 16.6 hours). Average doses of fentanyl and morphine sulfate received by patients were 13.5 μg/hour and 1.0 mg/hour, respectively. CONCLUSION: Elderly patients were very knowledgeable about how to use the PCA device but not about how often they could receive PCA medication. This lack of knowledge may have influenced how often they requested pain medication, because almost 90% of patients received less than 25% of the PCA allowable medication dose. This low usage of PCA medication delivery calls into question the cost-effectiveness of this method of medication delivery for the elderly. Additional studies are needed to verify these findings in other elderly patients.